Soldier of Tennessee General Alexander P. Stewart and the Civil War in the West - Elliott, Sam Davis (Louisiana State Univ. Press, 1999)
Stewart served in the Army of Tennessee from 1861 to its surrender in 1865, rising from major to lieutenant general. After the war he became chancellor of the University of Mississippi and the Confederate representative on the Park Commisiion at Chickamaunga-Chattanooga National Military Park.
Keywords: Stewart, Alexander Peter <1821-1908>; Stewart, Alexander Peter -- 1821-1908; Confederate States of America. -- Army of Tennessee -- Biography; USA -- Südstaaten -- Army of Tennessee; Amerikaanse burgeroorlog; Bevelvoering; Geschichte; Sezessionskrieg (1861-1865); Generals -- Confederate States of America -- Biography; Sezessionskrieg -- 1861-1865; USA; Georgia -- History -- Civil War, 1861-1865 -- Campaigns; Tennessee -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Campaigns; Biografie